Intercultural Financial Literacy and Cultural Orientation: Predicting Pay Later Behavior Among University Students in West Sumatra - Mia Muchia Desda; Ria Widia sari; Irna Bontor Febyola; Marlinda Saputri; Yuli Ardiany (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2026)
The development of the digital economy has given rise to the phenomenon of Buy Now, Pay Later (BNPL), which is popular among students but poses risks of consumptive behavior and unhealthy debt management due to low financial literacy and cultural awareness. This study aims to develop and test the Intercultural Financial Literacy (IFL) model as a new construct that combines financial literacy and cross-cultural awareness in explaining Pay Later usage behavior among students in West Sumatra. Using an explanatory quantitative approach with 300 respondents and Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis, the results show that IFL significantly influences financial attitudes and risk perceptions, which indirectly affect Pay Later behavior, while cultural orientation positively moderates this relationship. The research model explains 61.1% of the variation in digital financial behavior (R²=0.611) with good construct validity and reliability. These findings confirm that cross-cultural financial literacy is an important competency for the younger generation to shape ethical, responsible, and sustainable financial behavior in the pay later economy era.